EVALUASI PRAKTIKUM KIMIA UNTUK GURU SEKOLAH MENENGAH SE-RIAU: KAJIAN KEPUASAN DAN PENGUATAN KOMPETENSI PRAKTIS - Meidita Kemala Sari; Hasmalina Nasution; Sri Hilma Siregar; Prasetya Prasetya; Jufrizal Syahri; Rahmiwati Hilma; Rahmadini Syafri; Desi Asda Mora; Putri Apriliani Khorely (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
The Assisted School Program, launched by the Department of Chemistry at Universitas Muhammadiyah Riau (UMRI), aims to enhance the laboratory skills of high school chemistry teachers in Riau Province. The program addresses the need for stronger practical skills and a better understanding of laboratory safety, given limited access to modern equipment and current experimental methods in schools. Its primary goal is to provide teachers with technical and pedagogical competencies through project-based laboratory training in Laboratory Safety, Volumetric Analysis, Gravimetric Analysis, UV-Vis Spectrophotometry, and Adsorption.The program combined theoretical lectures, hands-on laboratory demonstrations, and pre- and post-test evaluations to measure knowledge gains. Twenty chemistry teachers from different schools in Riau participated. Results showed a significant improvement in post-test scores and high satisfaction levels. The overall service quality received an average rating of 4.95 out of 5, with the UV-Vis Spectrophotometry and Adsorption session achieving the highest satisfaction score of 4.80. No significant differences were found among schools, indicating the program’s equitable impact. These results demonstrate that the Assisted School Program effectively improves teachers’ professional competence, promotes safer, more modern laboratory practices, and provides a strong foundation for sustainable collaboration among universities, schools, and industry.